2021
DOI: 10.1029/2020jf005715
|View full text |Cite
|
Sign up to set email alerts
|

Locating Rockfalls Using Inter‐Station Ratios of Seismic Energy at Dolomieu Crater, Piton de la Fournaise Volcano

Abstract: Rockfalls generate seismic signals that can be used to detect and monitor rockfall activity.Event locations can be estimated on the basis of arrival times, amplitudes, or polarization of these seismic signals. However, surface topography variations can significantly influence seismic wave propagation and hence compromise results. Here, we specifically use the signature of topography on the seismic signal to better constrain the source location. Seismic impulse responses are predicted using Spectral Element bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…Recent studies have shown that important information related to the failure process and dynamics of rock mass movement can be acquired from seismic signals, such as the detection and differentiation of rock mass movement from seismic sources (Chen et al., 2013; Helmstetter & Garambois, 2010; Norris, 1994; Suriñach et al., 2000, 2005; Weichert et al., 1994; Zhu et al., 2016), precursor of instability (Duranteau et al., 2013; Hu et al., 2018; Schöpa et al., 2018), failure process (Deparis et al., 2008; Dietze et al., 2017), quick locating (Chang et al., 2021; Chen et al., 2013; Dammeier et al., 2015; Esposito et al., 2013; Hibert, Mangeney, et al., 2014; Jolly et al., 2002; Kao et al., 2012; Kuehnert et al., 2021; Yamada et al., 2012), force history (Allstadt, 2013; Ekstrom & Stark, 2013; Hibert, Ekström, & Stark, 2017; Hibert, Mangeney, et al., 2014), volume and velocity (Farin, Mangeney, et al., 2019; Hibert et al., 2011; Le Roy et al., 2019; Marc et al., 2016; Pérez‐Guillén et al., 2016; Yamada et al., 2012), grain interaction (Dammeier et al., 2015; Farin et al., 2018; Farin, Tsai, et al., 2019; Zhang et al., 2021), travel distance (Dammeier et al., 2011; Hibert, Stark, & Ekström, 2014) and other properties (Bottelin et al., 2014; Chang et al., 2021; Chao et al., 2016; Delannay et al., 2017; Farin et al., 2018, Farin, Mangeney, et al., 2019; Farin, Tsai, et al., 2019; Hibert, Ekström, & Stark, 2017, Hibert, Malet, et al., 2017; Vilajosana et al., 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that important information related to the failure process and dynamics of rock mass movement can be acquired from seismic signals, such as the detection and differentiation of rock mass movement from seismic sources (Chen et al., 2013; Helmstetter & Garambois, 2010; Norris, 1994; Suriñach et al., 2000, 2005; Weichert et al., 1994; Zhu et al., 2016), precursor of instability (Duranteau et al., 2013; Hu et al., 2018; Schöpa et al., 2018), failure process (Deparis et al., 2008; Dietze et al., 2017), quick locating (Chang et al., 2021; Chen et al., 2013; Dammeier et al., 2015; Esposito et al., 2013; Hibert, Mangeney, et al., 2014; Jolly et al., 2002; Kao et al., 2012; Kuehnert et al., 2021; Yamada et al., 2012), force history (Allstadt, 2013; Ekstrom & Stark, 2013; Hibert, Ekström, & Stark, 2017; Hibert, Mangeney, et al., 2014), volume and velocity (Farin, Mangeney, et al., 2019; Hibert et al., 2011; Le Roy et al., 2019; Marc et al., 2016; Pérez‐Guillén et al., 2016; Yamada et al., 2012), grain interaction (Dammeier et al., 2015; Farin et al., 2018; Farin, Tsai, et al., 2019; Zhang et al., 2021), travel distance (Dammeier et al., 2011; Hibert, Stark, & Ekström, 2014) and other properties (Bottelin et al., 2014; Chang et al., 2021; Chao et al., 2016; Delannay et al., 2017; Farin et al., 2018, Farin, Mangeney, et al., 2019; Farin, Tsai, et al., 2019; Hibert, Ekström, & Stark, 2017, Hibert, Malet, et al., 2017; Vilajosana et al., 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Despite their small volumes, rockfalls can still be catastrophic and can result in great human and economic losses due to their high frequencies, considerable impact forces, high velocities and unpredictable trajectories (Jaboyedoff et al., 2005, 2012; Rupp & Damm, 2020; Saroglou et al., 2018). Features of continuous seismic signals generated by rockfalls have been proposed as useful quantitative information sources for the real‐time monitoring and study of rockfall dynamics (Allstadt et al., 2018; Bottelin et al., 2014; Feng & Zhuang, 2021; Kuehnert et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The high-frequency signal is much more difficult to interpret, due in part to the strong effect of topography and Earth heterogeneity along seismic waves' path from source to receiver (Kuehnert et al, 2020(Kuehnert et al, , 2021. For this reason, mainly empirical relationships have been proposed between high-frequency signals and landslide characteristics (Allstadt et al, 2020;Dammeier et al, 2011;Deparis et al, 2008;Norris, 1994).…”
mentioning
confidence: 99%
“…However, the ambiguities arise in the case where there exist two velocity contrasts and a depth-dependent rise in shear wave velocity; under these conditions, the HVSR curve represents two peaks, and correct peak identification becomes challenging; this multi-peak conundrum has been described elsewhere [23]. Another associated with the interpretation of HVSR results is the influence of geomorphological features as topographic effects such as valleys, hills, basins etc., affect the seismic wave path, polarization and amplitudes [111]. As fluidization leads to change in the solid state, the assumption of a rigid body does not hold, and Newmark's approach doesn't apply in the case of a clayey landslide.…”
Section: Suitability Of Gm and Uav Methodsmentioning
confidence: 99%
“…The force inserted on the ground by the mega landslide was also determined using the force-time inversion approach [108,109]. The landslide event catalog so formed helps in the estimation of the probabilistic occurrence of such an event referred to as landquake (LQ) at a site, as well as an understanding of the triggering mechanism inferred by the correlation of meteorological factors with the so-formed catalogs [110,111].…”
Section: Gm and Ls Investigationmentioning
confidence: 99%